Fibrolamellar hepatocellular carcinoma complicating ulcerative colitis with primary sclerosing cholangitis. - Snook, J; Kelly, P; Chapman, R; Jewell, D (1989)
This case report describes the previously undocumented association between fibrolamellar hepatocellular carcinoma and ulcerative colitis complicated by primary sclerosing cholangitis.